Isolation and characterization of Candida Sps in people with chronic periodontitis - Desai , Karishma; RV Geetha, (International Journal of Psychosocial Rehabilitation, 2020)
Candida species are commonly found organisms in a normal healthy human being, they are considered normal flora. They are known to cause opportunistic infections with high mortality rates. Other Candida species apart from Candida albicans like Candida glabrata, Candida krusei, Candida dubliniensis, Candida parapsilosis, and Candida tropicalis have recently been discovered in infected individuals.For this study, 25 plaque samples were collected from the periodontics PG department of Saveetha dental college. The sampling was done randomly. The inclusion criteria for the sample was that the patient should have chronic periodontitis.The samples were cultured for the presence of Candida sps in Candida indicator agar.The results observed were that 4 out of the 25 plaque samples showed the growth of bluish green colonies. These bluish green colonies represent the growth of Candida albicans. 16% of the samples showed the presence of Candida species, mainly Candida albicans. Since 16% of the plaque samples taken from patients suffering from chronic periodontitis showed the growth of Candida albicans, it is necessary to take precautionary measures to avoid infections.